The delayed bloodstream clearance of Plasmodium falciparum parasites after M5717 treatment is attributable to the inability to modify their red blood cell hosts - Parkyn Schneider, Molly; Looker, Oliver; Rebelo, Maria; Khoury, David S.; Dixon, Matthew W. A.; Oeuvray, Claude; Crabb, Brendan S.; McCarthy, James; Gilson, Paul R. (Frontiers in Cellular and Infection Microbiology, 2023)
M5717 is a promising antimalarial drug under development that acts against multiple stages of the life cycle of Plasmodium parasites by inhibiting the translation elongation factor 2 (PfeEF2), thereby preventing protein synthesis. The parasite clearance profile after drug treatment in preclinical studies in mice, and clinical trials in humans showed a notable delayed clearance phenotype whereby parasite infected red blood cells (iRBCs) persisted in the bloodstream for a significant period before eventual clearance. In a normal P. falciparum infection iRBCs sequester in the deep circulation by cytoadherence, allowing them to avoid surveillance and clearance in the spleen. We found that M5717 blocks parasite modification of their host red blood cells (RBCs) by preventing synthesis of new exported proteins, rather than by directly blocking the export of these proteins into the RBC compartment. Using in vitro models, we demonstrated that M5717 treated ring/trophozoite stage iRBCs became less rigid, and cytoadhered less well compared to untreated iRBCs. This indicates that in vivo persistence of M5717 treated iRBCs in the bloodstream is likely due to reduced cytoadherence and splenic clearance.